Perceptions of Young Women about Breast Self-Examination - Hana Franciska Marida Uli Panjaitan; Masrina Munawarah Tampubolon; Rismadefi Woferst (CV. Rayyan Dwi Bharata, 2023)
Breast cancer is a relatively large health problem in Indonesia and other countries. The majority of sufferers are young, including adolescents. To overcome this, public health efforts are needed, namely through clinical and individual examinations. Breast self-examination (BSE) aims to find out if there are lumps in a woman's breasts. This qualitative descriptive research aims to explore the perceptions of adolescent girls about BSE. The research results obtained from seven participants obtained three themes, namely 1) digital media as the main source of BSE information, 2) adolescents' understanding of BSE and 3) the readiness and need for BSE education in adolescents. A good view of adolescent girls towards breast cancer is one of the factors that motivates them regarding efforts to detect early breast cancer (BSE). There is a need for more effective sexual health education, especially among adolescents who are more familiar with digital social media and demonstration methods. This research is expected to be the basis of information and evaluation material for readers regarding the optimization of breast health education strategies for adolescents.